Unleashing the Potential: A Comparative Analysis of K-Worker Competencies among Telkom University Cohorts - Teguh Iman Santoso; Danang Indrajaya (Journal of Industrial Engineering & Management Research, 2023)
Students must possess the necessary competences to work in the industrial sector. This study's aim is to suggest a worker competency model tailored to economic faculty students. Data from surveys given to economic faculty students are the basis for this quantitative study, which employs an explanatory study design. All students in the economic faculty make up the population. Convenience sampling was employed for the sample. All 1401 members of the economic faculty make up the research sample. The K-Workers Competency research tool from Santoso and Hasan's (2018) study is the one that was employed. Structural Equation Modelling (SEM) analysis utilizing SmartPLS 3 and Multi Group Analysis (MGA) were used to conduct the analysis. The SEM analysis reveals a well-adjusted K-Workers model for student perceptions, with 4 out of 6 hypotheses confirmed to be significant and 2 rejected. Competencies of K-Workers affect Telkom University students. These results can influence future curricula for students and are important in terms of theory, applicability, and policy making